Sit Still and Pay Attention! Trunk Movement and Attentional Resources in Infants with Typical and Delayed Development. (2nd January 2019) - Berger, Sarah E.; Harbourne, Regina T.; Guallpa Lliguichuzhca, Carmen L.
ABSTRACT: Aims : (1) examine infant movement during an early posture (sitting) utilizing a novel video assessment technique; and (2) document the differences between infants with typical development (TD), premature infants with motor delay, and infants with cerebral palsy (CP) during focused and nonfocused attention (NFA). Methods : Infants were tested when they began to sit independently. We utilized Eulerian Video Magnification (EVM) to accentuate small trunk and pelvic movements for visual coding from video taken during a natural play task with and without focused attention (FA). Results : Trunk/pelvic movement varied as a function of both motor skill and attention. Infants with TD and CP made fewer trunk movements during periods of FA than NFA. Preterm infants exhibited more trunk/pelvic movement than the other groups and their movement did not differ based on attention type. Conclusions : The EVM technique allowed for replicable coding of real-time "hidden" motor adjustments from video. The capacity to minimize extraneous movements in infants, or "sitting still" may allow greater attention to the task at hand, similar to older children and adults. Premature infants' excessive trunk/pelvic movement that did not adapt to task requirements could, in the long term, impact tasks requiring attentional resources.